2018
DOI: 10.1155/2018/3509091
|View full text |Cite
|
Sign up to set email alerts
|

Vildagliptin Attenuates Hepatic Ischemia/Reperfusion Injury via the TLR4/NF‐κB Signaling Pathway

Abstract: The Toll-like receptor-4 (TLR4)/nuclear factor kappa B (NF-κB) signaling pathway is vital in the pathogenesis of hepatic ischemia/reperfusion (HIR) injury. Dipeptidyl peptidase-4 (DPP4) inhibitors exert protective effects on IR injury of the kidney, heart, and lung; however, their effect on the liver is still unknown. Thus, the purpose of this study was to examine whether pretreatment with vildagliptin (Vilda), a DPP4 inhibitor, produces hepatic protection against IR injury and to investigate its influence on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 65 publications
10
32
0
Order By: Relevance
“…In the same line, a marked decrease in IL‐10 level was observed. These results coincided with other previous studies (Wang et al, ; Sherif and Al‐Shaalan, ). Therefore, interference with NF‐κB‐p65/TLR‐4 signaling pathway seems to play an important role in the protective effect of PER reported here, where pretreatment of rats with PER significantly down‐regulated the expression of TLR‐4 and NF‐ κ B‐p65 mRNA levels and subsequently reduced TNF‐ α and INF‐γ along with increased IL‐10 levels.…”
Section: Discussionsupporting
confidence: 94%
“…In the same line, a marked decrease in IL‐10 level was observed. These results coincided with other previous studies (Wang et al, ; Sherif and Al‐Shaalan, ). Therefore, interference with NF‐κB‐p65/TLR‐4 signaling pathway seems to play an important role in the protective effect of PER reported here, where pretreatment of rats with PER significantly down‐regulated the expression of TLR‐4 and NF‐ κ B‐p65 mRNA levels and subsequently reduced TNF‐ α and INF‐γ along with increased IL‐10 levels.…”
Section: Discussionsupporting
confidence: 94%
“…This effect can be explained by the activation of the first and second antioxidant defense lines, respectively, by the increase in SOD and CAT activities, which were also observed in this group (Figures 2A, 2B). Sherif et al showed that vildagliptin may increase CAT activity in the liver in rats with ischemic/reperfusion injury to this organ (41). The remaining two drugs also showed statistically significant reductions in reactive oxygen species ( Figure 1B, 1C) and an increase in SOD and CAT values (Figure 2A, 2B).…”
Section: Discussionmentioning
confidence: 89%
“…The activity of nitric oxide synthase is increased during ischaemic period with subsequent increase in NOx levels. NO reacts with the formed O2% during reperfusion to form peroxynitrite, leading eventually to cellular damage (Sherif & Al‐Shaalan, ).…”
Section: Discussionmentioning
confidence: 99%